Substituição tributária: sujeição passiva e dinâmica normativa - Rocha, Pedro Felipe de Oliveira (2019)
In this paper are investigated structure (HC) and meaning of the propositions placed at the antecedent (hypothesis) and at the consequent (consequence) of the legal rule of tax substitution, as well as the relationship between it and the other rules that are intertwined in its dynamic within the legal system. To approach and construct the formal object, was adopted the Logical-Semantic Constructivism as method and, as epistemological paradigm, the Philosophy of Language. The research starts from the semantic tying of concepts frequently used in the field of tax passive subjection. Basic concepts related to such instrument, found in the Federal Constitution of 1988 and in the National Tax Code, are also studied. Considering the solid basis of concepts, the objective of this study is the construction of the tax substitution legal rule (antecedent and consequent). It was found that its structure remains the same, being changed only its content according to the type of tax substitution. The legal rule of tax substitution always has in its consequent the propositional calculus between the relations that bind substitute-substituted and substituted-State, guaranteeing the emergence of the tax relation between State and substitute. Moreover, this legal rule, in its dynamic, relates to the rules of legal repercussion in order to guarantee the stabilization of the contributive capacity. It was found, therefore, that despite the traditional use of the term “substitution” to name the legal tool being studied, there‟s no substitution at all, only the creation of new relations, which explains the whole complexity of the theme